Elements of Transformational and Spiritual Leadership Communication in Imran Khan’s Speeches - Aslam, Muhammad zammad (2024)
The present study investigated the elements of transformational leadership (TL) and spiritual leadership (SL) in Imran Khan’s (hereafter, IK) speeches, specifically those he delivered at various international forums. The present study’s first aim was to determine the elements of TL and SL deducing from the theories. The second aim was to examine the elements of TL and SL, employing them in the communication of IK through content analysis of his speeches. After that, the third aim was to develop an SL communication model that may provide a guideline for future research on Muslim leadership communication at international forums (i.e., on other leaders from Muslim states). This qualitative study examined textual data trustworthiness using directed (deductive) qualitative content analysis (QCA). Notta premium was used to transcribe IK speeches (2008-2022) for directed QCA. The present study operationalised the directed QCA method by adapting and modifying it from the directed QCA approach developed by Assarroudi et al. (2018) and Kibiswa (2019). This adaptation/modification involved dividing the method into four distinct phases: sample design, data collection process, specifying the unit of analysis, and data analysis process. IK communicated differently in international forums than previous Pakistani leaders at international forums. IK employed religious references in his talks to influence his local and international followers, like other Pakistani political and religious leaders. TL and SL were conceptualised in this study; meanwhile, the findings found that basic elements of SL communication seemed present in his communication. However, IK primarily cited Islam and Islamic history in his communication with Islamic principles, knowing that the audience values a spiritual leader who speaks about religious teachings alongside political communication and understands the importance of religious spirituality. Hence, his SL communication may inspire local trust and optimism. However, he may mislead international audiences by incorporating religion into political speech. IK regularly used local spiritual elements in his communication to appeal to Pakistani/international followers’ religious beliefs. For the theoretical and practical contribution, the present study adds a novel approach for integration amongst three subfields of political communication: TL communication, SL communication, and religious SL communication that also reflects a Muslim socio-political perspective specifically in the context of political-cum-religious settings of Pakistan